2016
DOI: 10.1016/j.iheduc.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Cultural impacts on e-learning systems' success

Abstract: E-learning systems are enablers in the learning process, strengthening their importance as part of the educational strategy. Understanding the determinants of e-learning success is crucial for defining instructional strategies. Several authors have studied e-learning implementation and adoption, and various studies have addressed e-learning success from different perspectives. However, none of these studies have verified whether students' cultural characteristics, such as individualism versus collectivism (ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
1
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(123 citation statements)
references
References 73 publications
8
104
1
10
Order By: Relevance
“…Another study conducted by Islam (2013) in Finland, the author found that the students were mainly using the web-based learning system to download their course materials and submitting their assignments only. Furthermore, recent studies have shown that web-based learning system implementation is not simply a technological solution but also a process of many different factors, such as social factors (Tarhini, Hone, & Liu, 2014b;Aparicio, Bacao, & Oliveira;, organizational such as Facilitating Conditions (FCs) and individual factors such …”
Section: Introductionmentioning
confidence: 99%
“…Another study conducted by Islam (2013) in Finland, the author found that the students were mainly using the web-based learning system to download their course materials and submitting their assignments only. Furthermore, recent studies have shown that web-based learning system implementation is not simply a technological solution but also a process of many different factors, such as social factors (Tarhini, Hone, & Liu, 2014b;Aparicio, Bacao, & Oliveira;, organizational such as Facilitating Conditions (FCs) and individual factors such …”
Section: Introductionmentioning
confidence: 99%
“…A mixed design was used -one group of participants saw all the low stories, and the other saw all the high stories 1 . Within these groups, each participant saw five stories, one from each cultural dimension.…”
Section: Methodsmentioning
confidence: 99%
“…In this paper, we are particularly interested in adapting feedback to learners' cultural backgrounds. Cultural background has been shown to be important in the acceptance of user interfaces [17,10], information systems [2], and e-learning systems [1]. Researchers have highlighted that learners' cultural backgrounds affect their behaviours when using educational systems.…”
Section: Introductionmentioning
confidence: 99%
“…Hasil-hasil kajian sebelumnya juga memperkuat bahwa prose penggunaan metode belajar dan analisis pembelajaran yang menggunakan pendekatan teknologi memungkinkan anak untuk tertarik ikut serta dan memberikan kemudahan bagi guru sebagai fasilitator dalam melakukan evaluasi kedepannya (Ramdani, Widyastuti, & Ferdian, 2018;Wulan & Isnaeni, 2018). (Aparicio, Bacao, & Oliveira, 2016;Frijns, Dodd, & Cimerova, 2016;Legare & Nielsen, 2015;Mccrink & Shaki, 2016).…”
Section: Metode Paling Efektif Dalam Pembelajaran Sainsunclassified